2020
DOI: 10.1186/s13104-020-05097-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on HIV status disclosure to perinatal infected children: retrospective analysis of administrative records from a pediatric HIV clinic in the southern United States

Abstract: Objective: The World Health Organization recommends disclosing HIV-status between 6 and 12 years; American Academy of Pediatrics recommends that children are informed at "school age. " Neither suggests an optimal age when children should learn of their status to improve viral load suppression. Considering that virally suppressed people do not transmit HIV and that interrupting the transmission cycle is critical to ending the HIV epidemic, our objective is to examine the relationship between age of disclosure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Children who were disclosed to between aged 10 and 12 years had the highest rate of suppression (65%) compared with those disclosed to at younger than 10 years (56%) or older than 12 years (38%). 30 In the Thai study, there was no significant difference in the proportion with viral load <50 copies/mL between disclosed and nondisclosed children aged 6–12 years. 13 Moreover, in the study from Togo and Cote D'Ivoire of the 68 children disclosed to over the 24-month follow-up period, only 11 had viral load data and none achieved viral suppression (<50 copies/mL).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Children who were disclosed to between aged 10 and 12 years had the highest rate of suppression (65%) compared with those disclosed to at younger than 10 years (56%) or older than 12 years (38%). 30 In the Thai study, there was no significant difference in the proportion with viral load <50 copies/mL between disclosed and nondisclosed children aged 6–12 years. 13 Moreover, in the study from Togo and Cote D'Ivoire of the 68 children disclosed to over the 24-month follow-up period, only 11 had viral load data and none achieved viral suppression (<50 copies/mL).…”
Section: Discussionmentioning
confidence: 85%
“…Our finding is consistent with a retrospective study from Namibia using program data (N = 42) that found a 0.5 log 10 copied/mL decreased in viral load 12–24 months after disclosure intervention. 26 Interestingly, Budhwani et al 30 observed differences in age at disclosure and the rate of viral suppression in a pediatric clinic at University of Alabama in the United States. Children who were disclosed to between aged 10 and 12 years had the highest rate of suppression (65%) compared with those disclosed to at younger than 10 years (56%) or older than 12 years (38%).…”
Section: Discussionmentioning
confidence: 99%
“…While these disclosure rates were higher than several other cohorts of youth with perinatally acquired HIV, several included children as young as 6 years, and no others specifically identified youth born outside of the US. 24 In our analysis, the relationship between disclosure and care outcomes did not change when we included the entire cohort. In summary, our analysis provides an important overview of clinical outcomes among the predominant demographic group of youth with perinatally acquired HIV in the US -those born outside of the US.…”
Section: Discussionmentioning
confidence: 99%
“…5 One study from the Southern US highlights the importance of age, developmental status and contextually appropriate disclosure as youth with perinatally acquired HIV who learned of their status between 10 and 12 had the highest rate of viral suppression (65%) compared to peers who learned of their status younger (56%) or older (38%). 24 We restricted our analysis on disclosure to children greater than or equal to 12 years (who should have undergone complete disclosure according to WHO and American Academy of Pediatrics guidance). 5,22 Nearly three-fourths had undergone complete disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation